Multiaxial Universal Testing Machine (2004)
The invention concerns a multiaxial universal testing machine, which allows evaluating the mechanical behaviour and performance of materials with planar structures, such as fabrics, composites and laminates. The machine comprises 4 horizontal axes at 45°, with 8 gripping jaws displaceable along slide rails and moved by the action of 8 independent motors. The connection between a gripping jaw and its respective motor is assured by a linear actuator. The test specimen is fixed by the gripping jaws and can be subject to tensile, compression and fatigue testing, making possible the analysis of the materials behaviour under simultaneous multi-directional loads.